Urbanization and tuberculosis in Peninsular, Malaysia (2011-2015) - Kirandeep, Kulwant Kaur; Md Said, Salmiah; Poh, Ying Lim; Syed Ismail, Sharifah Norkhadijah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Tuberculosis (TB) is a major global concern as it continues to kill million people annually despite the availability of effective treatment. One of the social factors affecting the spread of tuberculosis is urbanization. Tuberculosis remains as the leading cause of death from communicable diseases in Malaysia for more than a decade. Geographic information system (GIS) has been used to understand the epidemiology of infectious diseases, to identify hot spots/ clusters of areas/ populations at high risk. The aim of this study was to determine the correlation between urbanization and TB in the Peninsular of Malaysia during 2011-2015 and develop TB incidence risk map using GIS. Methods: A cross-sectional study was conducted using TB cases data on tuberculosis incidence, tuberculosis deaths, urban population, population and population density from the Ministry of Health, Malaysia for the period 2011 to 2015. This data was analysed using SPSS version 23.0 and Arc GIS. Results: The number of TB cases and urbanization varied in the Peninsular. There was a statistically significant strong positive correlation between the number of TB cases and urban population (r=.884,p<.001). The highest mean of TB cases was recorded in Selangor (3922) while the lowest mean was in Perlis (146). Selangor state was noted to have the highest number of urban population and TB cases. Conclusion: The areas with higher urban population are at a higher risk of TB compared to those with low urban population.